Aging phenomena in non-crosslinked polyolefin blend cable insulation material: Electrical treeing and thermal aging - Lunzhi, Li; Jinghui, Gao; Lisheng, Zhong; Kai, Zhang; Xiaohan, Zhao (Frontiers in Chemistry, 2022)
Owing to its low power consumption in production process and good recyclability at the end of life cycle, non crosslinked polyolefin blends has become a favorable alternative material to XLPE cable insulation. Although researches on non-crosslinked materials have achieved intensive results, there is much work remains to be done especially on electrical and thermal aging properties. Aging performance is directly related to the lifetime and reliability of cables. In this paper, the electrical treeing and thermal aging phenomena of 70wt% linear low density polyethylene (LLDPE) and 30wt% high density polyethylene (HDPE) blends (abbreviated as 70L-30H) have been studied and compared with XLPE by investigating the microstructure feature, electrical treeing behavior and mechanical performance in thermal aging. Electrical treeing tests show that the 70L-30H blends has smaller treeing dimensions as well as lower electrical tree growth rate than that of XLPE. Thermal aging tests exhibit that the mechanical properties degradation of 70L-30H blends is less than that of XLPE under the same aging time. Through DSC analysis and microstructure observation, the 70L-30H blend shows higher melting temperature, thicker lamellae and higher crystallinity with uniform fine-spherulite structure, which are responsible for good anti-aging performance. Our work suggests that the blends emerges better electrical and thermal aging resistance than XLPE, which will provide performance guarantee for its further application in non-crosslinked cable system.